Field Vegetable Production in Hungary - Kristóf, E.; Terbe, I. (International Journal of Horticultural Science, 2002)
Hungary is a country with excellent ecological potentials and with rich traditions in vegetable production. The total vegetable production area comprises about 100 000 ha and annual production amounts to 1.4-1.8 million tons, 75-80% comes from fields and the rest from forcing. Approximately 40 species are produced, but only 20 of them play a dominant role. The most important ones arc: sweet corn, peas, peppers, watermelon, onions, tomatoes, gherkin, carrots, beans, white cabbage. 40-45% of the total production is processed, 20-30% sold on the fresh market and 30% exported. Vegetable production is based on rural farms of 1-5 ha average acreage. It provides living for about 70-100 000 families. The low number of producers’ organisations is a major setback. Profitability of vegetable production is rather low. Production costs are high, wholesale prices are depressed. Vegetables are produced for the industry by contract. Fresh vegetables are sold through local markets (15-20%), the wholesale market (decreasing importance) and direct marketing (35-40%). Against the self-sufficiency of the country there is a seasonal import of vegetables mainly in winter and early springtime. Hungarian legal regulations are harmonized with the EU directives, EU standards are accepted and applied, traditionally good market connections and cooperation with several EU countries enable the country to be a partner of EU vegetable growers.